Assessment and Modeling of Household-Scale Solar Water Heater Application in Zambia: Technical, Environmental, and Energy Analysis - Mehdi Jahangiri; Esther T. Akinlabi; Sam M. Sichilalu (International Journal of Photoenergy)
Solar water heaters (SWHs) are one of the most effective plans for general and easy use of solar energy to supply hot water in domestic and industrial sectors. This paper gives the first-ever attempts to assess the optimal localization of SWHs across 22 major cities in Zambia, as well as determine the possibility of hot water generation and model the greenhouse gas (GHG) emission saving. The climate data used is extracted by using the MeteoSyn software which is modeled in TSOL™. Results show the high potential of GHG emission reduction due to nonconsumption of fossil fuels owing to the deployment of SWHs, and three cities Kabwe, Chipata, and Mbala had the highest GHG mitigation by 1552.97 kg/y, 1394.8 kg/y, and 1321.39 kg/y, respectively. On average, SWHs provide 62.47% of space heating and 96.05% of the sanitary hot water requirement of consumers. The findings have shown the potential for the deployment of SWHs in Zambia. The techno-enviro study in this paper can be used by the policymakers of Zambia and countries with similar climates.